Chromosomal abnormalities in children as a predictor of the development of congenital heart and vascular diseases - Z.V. Selska; O.R. Sadova; V.I. Bobrova; K.E. Popov (Сучасна педіатрія: Україна)
Congenital heart defects (CHDs) are the most common of all congenital abnormalities in children and cover a wide range of lesions. They can manifest as minor defects and very complex combined lesions that are incompatible with life. CHDs occur on average in 8-10 cases per 100 live births. The complexity and diversity of cardiovascular defects is traditionally explained by multifactorial etiology, due to the interaction between several genes and environmental factors (the so-called “polygenic model”), but chromosomal abnormalities are often the leading factor in the occurrence of CHDs. The importance of studying chromosomal pathology in the context of CHD lies in the possibility of identifying specific genetic markers that are predictors of the development of these conditions.